STRENGTHENING THE NECK AND SHOULDER GIRDLE MUSCLES IN BASKETBALL PLAYERS AGED 14 – 15 DURING THE COVID-19 PANDEMIC - Škutāne, Sandra; Galeja, Zinta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
During the COVID – 19 pandemic, opportunities for sport activities are limited and studies take place in front of the computer. Computer and telephones are an essential component of life among the youth aged 14-15, when school studies take place online. The human body tries to adapt to these changes. Over the past few years, a growing number of authors have studied the “text (message) neck syndrome,” which can be considered the new syndrome of the twenty-first century. In studies, the normal angle of the neck is considered to be 52°. At the beginning of our studies, we obtained the following indicators: the average angle of the neck was 56,04°, and the average angle of the shoulder was 49,34°. The disciples have been performing a set of 20 exercises during the study, which lasted for one month. In the repeated tests, we have obtained the following indicators: the average angle of the neck was 53,46°, and the average angle of the shoulder was 45,19°. Albeit the angle indicators are within the normal range, the indicators went down during the distance studies. We also drew the disciples’ attention to the protracted shoulders (PSs). Aim of the study: to develop a set of exercises to strengthen the neck and shoulder girdle for basketball players aged 14 – 15 for improving posture and preventing the “text neck syndrome.”Methods: Analysis of literature sources and scientific studies. Measuring experiment. Photogrammetry. Mathematical statistical analysis.